ABOUT TASHPOLAT AHMAD’S EPIC WRITING SKILLS - Nizomova, Kamola Vahid qizi (Educational Research in Universal Sciences, 2023)
This article analyzes the epic poem "Ustoz Hafiz va Shinavanda Shah" written by Tashpolat Ahmed, a talented poet from Bukhara and a cultural worker in Uzbekistan, and as well as it reveals the poet’s epic writing skills.